Isolation and identification of osmophilic yeasts from Indonesian honeys collected from South Kalimantan, Banten, and East Java Provinces (Indonesia) - MEILIA PRIHARTINI; SYOFI ROSMALAWATI; CATUR SRIHERWANTO; ANIS HERLIYATI MAHSUNAH (Society for Indonesian Biodiversity, 2023)
Abstract. Prihartini M, Rosmalawati S, Sriherwanto C, Mahsunah AH. 2023. Isolation and identification of osmophilic yeasts from Indonesian honeys collected from South Kalimantan, Banten, and East Java Provinces (Indonesia). Biodiversitas 24: 4126-4135. Certain yeasts possess the remarkable ability to thrive in the challenging conditions characterized by high sugar levels and low water activity commonly found in honey. However, limited research has been conducted on yeasts isolated from honey in Indonesia. To address this gap, honey samples were collected from three provinces in Indonesia: South Kalimantan, Banten, and East Java. A total of ten isolates were obtained and subjected to comprehensive morphological, physiological, and biochemical characterization. Among these isolates, four (M 1.4, M 1.6, M 1.8, and M 2.4) were selected for molecular identification using ITS1 and ITS4 primers. Through sequencing of the Internal Transcribed Spacer (ITS) region and performing homology analysis using BLAST on NCBI, it was determined that the M 1.4 and M 1.8 isolates belong to the Zygosaccharomyces genus with a percentage identity of ?97%. The M 2.4 isolate was classified as the Schizosaccharomyces genus with a percentage identity of ?98%, while the M 1.6 isolate was identified as Zygosaccharomyces siamensis with a percentage identity of ?99%. All four isolates exhibited osmophilic characteristics and demonstrate significant potential as valuable microorganisms for future investigations.